Correlation analysis and clinical significance of changes in upper thoracic vertebra tilt and clavicle angle pre- and post-operation - Jiang, Zhensong; Wang, Haoyu; Cui, Ran; Wang, Xingpeng; Wang, Yunhui; Sun, Mingtong; Peng, Fushuai; Li, Tao; Zhang, Weimin; Zhang, Wen (Frontiers in Surgery, 2024)
The imbalance of the lateral shoulder is reflected by the clavicle angle (CA) in radiology. It remains unclear how to achieve postoperative lateral shoulder balance (LSB) after spinal deformity correction surgery. A retrospective analysis was conducted on AIS patients who underwent surgery by the same spine surgeon at our hospital from 2016 to 2020. A total of 110 patients with spinal deformity were included in the study to verify the correlation between the T1-T5 tilt angle and CA before and after surgery, as well as the relation-ship between the change in T1-T5 tilt angle before and after surgery and the change in CA before and after surgery. By comparing the correlation coefficients, it was found that there may not be a direct relationship between the pre-and postoperative tilt angles of T1-5 and CA, but their changes were closely related to the changes in CA. The change in T1 tilt angle after orthopaedic surgery was significantly correlated with the change in CA, with a correlation coefficient of 0.976, indicating a close relationship between T1 and the clavicle. As the vertebrae moved down, the correlation gradually decreased. In summary, this study suggests that there is a close relationship between T1-T5 and the clavicle and that the change in T1 tilt angle after spinal scoliosis correction surgery is significantly correlated with CA, which decreases as the vertebra moves down.